Navigating Uncertainty: The Role of Digital Assets - Husain, Afzol (Global Review of Islamic Economics and Business, 2023)
This research studies the dynamic connectedness among digital assets proxied by non-fungible tokens (NFTs), Islamic cryptocurrencies, and conventional cryptocurrencies with the US Economic Policy Uncertainty (EPU) and Geopolitical Risk (GPR) indices. We also examine the hedge and safe haven properties of the aforementioned digital assets against the uncertainties. Using wavelet coherence analysis from 19 January 2018 to 31 October 2023, we show that NFTs react heterogeneously to changes in uncertainties while cryptocurrency reacts inversely. NFTs and conventional cryptocurrencies can only act as diversifiers, but neither as a hedge nor a safe haven against uncertainties. However, Islamic cryptocurrencies have the potential to act as both a hedge and a safe haven against uncertainties. Our findings shed light on the role of emerging digital assets in formulating investment strategies and ensuring stability in the financial markets. Originality/Value: Given the immense potential of digital assets, a remaining research gap concerns their interplay with uncertainty. In other words, given the presence of extreme market turmoil over recent years, no consensus is present in terms of highlighting the dynamic co-movement between digital assets such as NFT, Islamic cryptocurrencies, and global uncertainty factors. In addition to that, the lead-lag relationship among digital assets and uncertainties are also unknown till date. The current study fills this gap by providing robust evidence.